Probing allosteric coupling in a constitutively open mutant of the ion channel KcsA using solid-state NMR - Sun, Zhiyu; Xu, Yunyao; Zhang, Dongyu; McDermott, Ann E. (Proceedings of the National Academy of Sciences - PNAS, 2020)
Transmembrane allosteric coupling is a feature of many critical biological signaling events. Here we test whether transmembrane allosteric coupling controls the potassium binding affinity of the prototypical potassium channel KcsA in the context of C-type inactivation. Activation of KcsA is initiated by proton binding to the pH gate upon an intracellular drop in pH. Numerous studies have suggested that this proton binding also prompts a conformational switch, leading to a loss of affinity for potassium ions at the selectivity filter and therefore to channel inactivation. We tested this mechanism for inactivation using a KcsA mutant (H25R/E118A) that exhibits an open pH gate across a broad range of pH values. We present solid-state NMR measurements of this open mutant at neutral pH to probe the affinity for potassiumat the selectivity filter. The potassium binding affinity in the selectivity filter of this mutant, 81 mM, is about four orders of magnitude weaker than that of wildtype KcsA at neutral pH and is comparable to the value for wild-type KcsA at low pH (pH ≈ 3.5). This result strongly supports our assertion that the open pH gate allosterically affects the potassium binding affinity of the selectivity filter. In this mutant, the protonation state of a glutamate residue (E120) in the pH sensor is sensitive to potassium binding, suggesting that this mutant also has flexibility in the activation gate and is subject to transmembrane allostery.